2002
DOI: 10.1063/1.1483604
|View full text |Cite
|
Sign up to set email alerts
|

On the Measurement of Shear-Strength in Quasi-isentropic Loading

Abstract: It has been a subject of discussion that the rate of loading of a material determines the strength it appears to exhibit. This observation has implications for understanding and modelling the deformation mechanisms involved in high-strain rate and shock-loading. Discussion has focussed upon the response of various metals. The loading has ranged from prompt shock to pillow loads (graded density impactors) which give uniformly rising pulses over varying times. One variant upon such loading is to allow the stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 5 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…Much higher strengths are surprising, and appear to be in error [49]. In part to address the validity of the Bat'kov et al results, Rosenberg et al [63] loaded copper, iron, and mild steel using a ''ring-up'' technique. Though the error bars were rather large, they found that the shear stress of copper was essentially the same for shock and isentropic loading to nearly 12 GPa.…”
Section: Strength Under Isentropic Loadingmentioning
confidence: 99%
“…Much higher strengths are surprising, and appear to be in error [49]. In part to address the validity of the Bat'kov et al results, Rosenberg et al [63] loaded copper, iron, and mild steel using a ''ring-up'' technique. Though the error bars were rather large, they found that the shear stress of copper was essentially the same for shock and isentropic loading to nearly 12 GPa.…”
Section: Strength Under Isentropic Loadingmentioning
confidence: 99%
“…The rise time of the trace obtained from the grid and T gauges were ∼1.3 µs and ∼0.1 µs, respectively. In order to take advantage of the superior rise time of the T gauges, dynamic strength measurements have been made using grid gauges to measure the longitudinal stress and T gauges to measure the lateral stress (see, for example, Rosenberg et al [5]). However, a possible disadvantage with this scheme is that the construction of the two gauges are significantly different and therefore the processes controlling the resistance changes of the gauges may be different.…”
Section: Introductionmentioning
confidence: 99%